Bemühungen des Adels böhmischen Nordostes um Folgenverminderung der Konfiskationen nach der Schlacht am Weissen Berg (Theatrum historiae, 2012)
This study analyses the situation of several selected noble families from within the Hradec Králové Province, the members of which were punished by the property sanctions after the uprising of Bohemian estates in the 17th century. The research documented general characteristic features accompanying the restitutional efforts of the fined and punished nobles as well as of the persons related to them. Among these general features rank e.g. the high number of persons affected through one confiscational case (wives, widows, children, relatives, descendants), the considerable degree of the indebtedness burdening the confiscated properties which further broadened the circle of affected persons by a significant number of creditors. Furthermore, the protracted administrational procedure of the examination of pleas presented by the supplicants and also the way of legal argumentation of the respective committees, the court chamber and the attorney appears to have been consistent and in conformity with the provisions of law. The individual discoveries from research illustrate different possibilities of the supplicants to conduct negotiations and the applied tactics. This concerns mainly reconstructions of the social bonds and explanations of their significance for the speed of the decision-making processes of the clerks and officers in the matters of the presented pleas. Other aspects involved are the role of intercessors, legal advisors or, on the other hand, the influence and status of persons aiming at the gain of the confiscated properties.
Keywords: post-White Mountain confiscations; restitutions; nobility; The Hradec Králové Province; the 17th century